Incidencia del periodismo digital en la formación de los futuros profesionales en comunicación social de la Universidad Nacional de Loja, periodo septiembre 2010 – febrero de 2011. - Neira Calderón, David Alejandro (2013)
This research work that is presented below, looking back to the subject of the so-called information age. The way to learn and communicate has changed significantly in the last two decades. The trends in new communication technologies are influencing the way to learn from people, and this forces to modernize both the coverage of information and style of writing and publishing the news. The challenge of the new communicator must be more analytical and attached to the reality of the facts, now smartphones allow greater flexibility in making known events. In Ecuador, some media have realized and try to implement features of digital journalism to its environment. However, the new technologies of communication is not considered sufficient as their digital media do not meet all the necessary features to achieve this. Due to new communication technologies and how they affect the way journalism is done in the Internet platform, this thesis aims to promote digital journalism as part of the professional training of journalists, establish their knowledge communicators on the subject and evaluate technological tools that the communicator must know to develop as professional journalism. Social networks are a means to inform the mass media have adopted this alternative as the platform for publishing news that serve short link to visit their official websites which offers extensive information, which makes it necessary for the students of the School Communication know these alternatives and put them to the service of his professional practice and future of an entire group. Under it is argued that communication studies included in the curriculum of the races of Journalism and Mass Communication, the themes related to new information technologies and offer majors in journalism to be at the forefront of current trends and technology journalism.